CHEMICAL SENSOR WITH CONDUCTIVE CUP-SHAPED SENSOR SURFACE - BUSTILLO, James; HINZ, Wolfgang; LI, Shifeng (2017)
A system includes a sensor including a sensor pad and a well wall structure defining a well operatively coupled to the sensor pad. The well is further defined by a lower surface disposed over the sensor pad. The well wall structure defines an upper surface and defines a wall surface extending between the upper surface and the lower surface. The system further includes a conductive layer disposed over the lower surface and the wall surface.